Coloring of Polyhedral Regular and Irregular Fuzzy Graphs - K, Kalaiarasi; L, Mahalakshmi (International Journal of Computer Sciences and Engineering, 2018)
In this article we propose coloring of polyhedral regular and irregular fuzzy graphs.Also we have investigate some new concepts of polyhedral fuzzy graphs,Planar fuzzy graphs and coloring of polyhedral regular and irregular fuzzy graphs.We anayze some basic theorems related to these concepts.